Home at work: households and the structuring of women's employment in late nineteenth century Dundee - Crockett, Nicole J. (The University of Edinburgh, 1994)
The past decade has witnessed a debate in the literature over the best way to explain patterns of gender inequality. The central objective of contributions has been to understand the processes which underlie differences in the experiences of men and women. Particular concern is directed at processes which lead to women's unpaid labour in the home and to their position vis-a-vis men, in paid employment where they are found in segregated and low paid occupations. Theoretical developments range from dual systems approaches, which try to explain gender by combining a theory of patriarchy with a Marxist theory of capitalism, to approaches which argue for a single integrated explanation of production and reproduction. This thesis assesses these developments and finds current understandings lacking in two respects. Firstly, although there is a recognition of the inadequacy of Marxist categories in accounting for gender they are, none the less, given a central place in explanations. Similarly, variations in the experience of men and women are often discussed but are rarely incorporated into theoretical explanations as significant categories. A large part of the problem stems from the abstract level at which the development of explanations has been carried out. The argument presented here is that advances in theoretical explanation require that the processes underlying patterns of gendered experience are properly identified, and that this can only be achieved by thorough empirical examination of the wider context in which women labour. Those contributing to the debate have focused on a few symbolic occurrences in the nineteenth century such as protective legislation, male trade union exclusivism and the family wage. In a study of Dundee, a Scottish textile city, the broader context of everyday life is explored for women working in the industry during the late nineteenth century. To begin with information on wages is matched to occupations enabling the hierarchy of women's textile jobs to be established. Dundee provides a unique opportunity to look at a variety of households, and here the composition of households from a sample of the 1891 Census is outlined and the distinctive features of those headed by women are discussed. The structure of households which emerges from this exercise is related to the structure of occupations, making it possible to identify processes of inequality which are composed of household/employment experiences. In the Dundee sample processes of this sort are found to be of great importance in gaining access to employment. The structure of opportunity which exists and the patterns of inequality associated with it have consequences for what people are required to do in order to make ends meet.